2007
DOI: 10.1165/rcmb.2006-0178oc
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Myofibroblastic Differentiation and Survival in Thy-1(−) Lung Fibroblasts

Abstract: Thy-1 is a glycosylphosphatidyl-inositol-linked cell surface glycoprotein whose exact biological role remains unclear. Differential expression of Thy-1 affects fibroblast proliferation and fibrogenic signaling. In idiopathic pulmonary fibrosis, the proliferating myofibroblasts within the fibroblastic foci are Thy-1(-), whereas normal lung fibroblasts are predominantly Thy-1(+). In this study, we used rat lung fibroblasts sorted for Thy-1 expression to examine myofibroblastic differentiation in response to fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
129
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 45 publications
11
129
0
Order By: Relevance
“…7 Heterogeneous surface expression of Thy-1 in fibroblasts results in the specialization of fibroblast, including Thy-1 (+) and Thy-1 (− ) subsets. Hagood et al 5,8,9 reported that lack of Thy-1 expression on lung fibroblasts contributed to IPF. Recently, it was found that epigenetic mechanisms, such as promoter hypermethylation and histone modification, play an important role in Thy-1 gene silencing in lung fibroblasts.…”
mentioning
confidence: 99%
“…7 Heterogeneous surface expression of Thy-1 in fibroblasts results in the specialization of fibroblast, including Thy-1 (+) and Thy-1 (− ) subsets. Hagood et al 5,8,9 reported that lack of Thy-1 expression on lung fibroblasts contributed to IPF. Recently, it was found that epigenetic mechanisms, such as promoter hypermethylation and histone modification, play an important role in Thy-1 gene silencing in lung fibroblasts.…”
mentioning
confidence: 99%
“…These Thy-1 (Ϫ) lung fibroblasts exhibit increased motility, contractility, and expression of myofibroblastic characteristics as compared with Thy-1 (ϩ) cells. [12][13][14][15][16] TGF-␤ bioavailability is regulated by complex factors, including agents that control activation, synthesis and processing, and deposition in the extracellular matrix (ECM). 17 Latent TGF-␤ binding proteins (LTBP-1, -2, -3, and -4) are a family of fibrillin-like molecules that contain multiple unique 8-cysteine repeats and multiple EGF-like domains.…”
mentioning
confidence: 99%
“…To this end, E12.5-E13.5 MEFs were FACS-sorted into four phenotypically distinct subpopulations based on the surface expression of Thy1 (CD90) and Sca1 (stem cell antigen 1) markers. Previous studies demonstrated that Thy1 expression defines lipofibroblastic or myofibroblastic lineage, 26 while Sca1 is a marker specifying murine mesenchymal and epithelial progenitor cells. 27 Our microarray analyses confirmed that Sca1-single-positive cells (SP) express genes broadly involved in embryonic and tissue morphogenesis, thus indicating their immature origin (Supplemental Table 1), whereas Thy1/Sca1-doublenegative (DN) cells selectively express markers of myofibroblast-committed progenitors (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 99%